Bio-Based Value Chains Potential in the Management of Cacao Pod Waste in Colombia, a Case Study - Diana C. Meza-Sepúlveda; Ana M. Castro; Annie Zamora; Jorge W. Arboleda; Adriana M. Gallego; Anyela V. Camargo-Rodríguez (Agronomy, 2021)
Agriculture generates 11.4 billion tons of biomass worldwide, including residues from crop production and industrial processing. Improper disposal of agricultural residues results in environmental pollution and the waste of valuable biomass resources. Management of agricultural waste is particularly suboptimal in developing countries where low added-value traditional practices to manage the residues are commonplace. A bioeconomy approach to better manage agricultural waste is to use renewable biological resources from land and sea to produce new materials and energy, allowing the development of bio-based value chains (BBVC). This study explored the potential of BBVC in the management of cacao pod husk (CPH), the primary residual biomass generated from the production of cacao in Colombia. Thus, a literature review on cacao pod husk (CPH) management strategies and a survey for farmers from Caldas State in Colombia between August and November of 2020 were performed to identify the potentials and limitations of BBVC in the management of CPH. Assessment of CPH management strategies suggested variable uses for CPH categorized in energy, food, and miscellaneous. Analysis of surveys indicated farmers are keen to implement strategies to better manage their agricultural waste, but that information is not available to them. Finally, an approach to develop a BBVC from cacao was proposed, which we plan to implement as a future research direction. We expect to impact the economic growth positively in the region with bio-based products in the market.